2021
DOI: 10.3892/ijmm.2021.4881
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic mechanism activated by blue light and cisplatinum in cutaneous squamous cell carcinoma cells

Abstract: New approaches are being studied for the treatment of skin cancer. It has been reported that light combined with cisplatinum may be effective against skin cancer. In the present study, the effects of specific light radiations and cisplatinum on A431 cutaneous squamous cell carcinoma (cScc) and HacaT non-tumorigenic cell lines were investigated. Both cell lines were exposed to blue and red light sources for 3 days prior to cisplatinum treatment. Viability, apoptosis, cell cycle progression and apoptotic-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Cisplatin induces DNA damage and a slight degree of G2/M phase arrest leading to the apoptosis of proliferating cells. 38 The TPE-s COF-Au@Cisplatin group triggered cell division and boosted the S phase compared to the untreated control cells. Combined treatment with M@TPE-s COF-Au@Cisplatin + laser group exhibited lower percentages of cells in the G0/G1 and higher ones in the G2/M phase ( Figures 3 D and 3E).…”
Section: Resultsmentioning
confidence: 93%
“…Cisplatin induces DNA damage and a slight degree of G2/M phase arrest leading to the apoptosis of proliferating cells. 38 The TPE-s COF-Au@Cisplatin group triggered cell division and boosted the S phase compared to the untreated control cells. Combined treatment with M@TPE-s COF-Au@Cisplatin + laser group exhibited lower percentages of cells in the G0/G1 and higher ones in the G2/M phase ( Figures 3 D and 3E).…”
Section: Resultsmentioning
confidence: 93%
“…High-irradiance red light did not induce cell death and did not alter the clock gene expression levels. Indeed, it was confirmed that the effects due to high-irradiance blue light exposure in the HaCaT cells were more toxic than those of high-irradiance red light [23]. The toxic effect of blue light on keratinocytes can be prevented by chemicals acting on inflammation and oxidative stress [37].…”
Section: Discussionmentioning
confidence: 92%
“…Blue light, as a visible light with a wavelength range of 400–500 nm, has been clinically applied successfully comprising neonatal jaundice, psoriasis (Pv), atopic dermatitis (AD), eczema, acne, and other inflammatory skin conditions, although the number of available clinical studies evaluating the efficacy of blue light treatment is still limited ( 103 , 136 ). Furthermore, recent studies have demonstrated that blue light irradiation inhibits the proliferation of multiple types of cancer cells in vitro and in vivo , including colon cancer cells ( 14 , 144 , 145 ), malignant glioma cells ( 12 ), melanoma cells ( 10 , 146 , 147 ), B-cell lymphoma cells ( 13 ), fibrosarcoma cells ( 14 ), pancreatic cancer cells ( 15 ), cutaneous squamous cell carcinoma cells (CSCC), epidermoid carcinoma cells ( 148 , 149 ), leukemia cells (Kasumi-1) ( 150 ), bladder cancer cells ( 151 ), colorectal cancer cells ( 152 , 153 ), breast cancer cells ( 91 ), and human OS cells ( 95 , 98 ). Here, we have briefly summarized the relevant research of blue light PBMT in the field of cancer treatment ( Table 1 ).…”
Section: Blue Light Photobiomodulation Therapy In Cancer Treatmentmentioning
confidence: 99%